Vertical and horizontal networks revisited: exploring their effects on attitudes and advocacy toward nuclear energy - Satoh, Keiichi; Weiß, Tobias (Social science Japan journal, 2021)
After the Fukushima accident, Japan experienced a drastic decline in nuclear energy use because of resistance from civil society. This civil society activity can be explained by the strong social capital forged in Japanese communities. By contrast, the classical (and some recent) literature has argued that Japan’s dense network of associations and groups functions to disseminate conservative ideology and thus control civil society. The classical school of thought has described networks of conservative organizations as vertical in contrast to horizontal networks. This article explores the empirical evidence in this discussion by analyzing the effect of affiliation of each type of group on the members’ attitude and advocacy toward nuclear energy policy based on our survey (n = 77,084) conducted in late 2017. Detailed analysis of group effects of relevant group features led us to reconceptualize the aforementioned dichotomy. Vertical networks are often associated with groups’ conservatism but vary in the degree of postmaterialism and activism. Each dimension of group features has different effects on members’ opinions of nuclear energy, sentiment toward antinuclear movements, and antinuclear advocacy. Neither social capital theory nor vertical network theory is fully confirmed by this study. Both effects can be observed in different segments of respondents. (Soc Sci Jap J/GIGA)
Keywords: Japan